An overview of sheep farming features and management practices in the region of south western Peloponnese and how they reflect on milk microbial load - MANOLOPOULOU, E.; AKTYPIS, A.; MATARA, C.; TSIOMI, P.; KONSTANTINOU, E.; MOUNTZOURIS, K.; KLONARIS, S.; TSAKALIDOU, E. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this study the demographic features, various farm characteristics and milk quality parameters were investigated in sheep farms (n =128) from the North West Peloponnese region, using a prescreen questionnaire. The interviewed sheep farmers were under the control of the regional milk control laboratory of the Hellenic Milk Organization ELGO «Dimitra», which provided us with the corresponding milk quality data for the first quarter of 2014. Our findings regarding the demographic data demonstrated that 23% of farmers were 31-40 years old, 64% of them were high school graduates and 28% had received relevant farming general training; namely 17% of them has designated as “young farmers” in the frame of Third Axis of the Operational Program «Rural Development-Regeneration of the Countryside 2000-2006» and 11% have attended briefings by veterinarians and agriculturists. Ιn terms of farm characteristics, it has been revealed that the mean flock size was 148 sheep and regarding the farming system, the majority of the farms (89.15%) applied a mixed extensive / indoors system. Additionally, regarding building infrastructures and the way of milking, there was limited technological penetration, since the buildings were old-style (77%) and the milking procedure was performed by hands (83%). Concerning the milk composition, the measurements showed mean values of (%) content of fat, protein, lactose and non-fat dry matter (NFDM) at 6.54±0.88, 5.56±0.36, 4.59±0.23 and 10.95±0.42, respectively. Furthermore, the mean value of the total bacterial count (TBC) was found 5.38±0.55 log cfu/ml and the pH value at 6.71±0.11. In general, sheep farmers had a good perception of the integrated management and their prospect for sheep farming was optimistic. The impact of this study is that farmers increase their trust to the educational institutions and are prompted to become more receptive to new adaptive trends.